Evaluation of fluxgate magnetometry and electromagnetic induction surveys for subsurface characterization of archaeological features in World War 1 battlefields. Issue 2 (3rd December 2018) - Note, Nicolas; Saey, Timothy; Gheyle, Wouter; Stichelbaut, Birger; Van den Berghe, Hanne; Bourgeois, Jean; Van Eetvelde, Veerle; Van Meirvenne, Marc
Abstract: Geophysical prospection as a noninvasive archaeological survey technique has become a widely applied discipline that is currently finding its way into the former World War 1 (WW1) battlefields. Because of the imminent danger of unexploded ordnances, noninvasiveness is the key to exploring the subsurface containing our buried heritage. Fluxgate magnetometry (FGM), a frequently applied prospection technique in archaeology and unexploded ordnance detection, is not always satisfactory in this area. This is due to the high density of ferrous objects masking the underlying features of interest. Frequency domain electromagnetic induction (EMI) has proved to be less sensitive to metal objects, thereby revealing more WW1 traces. Another advantage of EMI is that soil disturbances related to shelling and metal objects can be classified with higher precision by combining magnetic and electrical conductivity data layers. After evaluating both prospecting techniques on maximum feature coverage, feature type identification, metal object filtering, and localization, EMI was shown to be the most successful. Although FGM is not inferior (providing high survey speed and density with multisensor arrays and reliability in pinpointing features, etc.) overall, EMI is the preferred option on sites with heavily disturbed soil. In this paper, these findings will be demonstrated with survey examples, case studies, and numerical analyses from the WWI battlefields of Flanders.